Prevalence of Serum Vitamin B12 Levels among Patients Presented to Hebron Charitable Medical Center, Palestine - Amro, Nawaf RN; Masalma, Abbas (International Journal of Innovative Research in Medical Science, 2017)
Background: Vitamin B12 is an essential element for proteins, phospholipids metabolism and neurotransmitters synthesis. It also plays a key role in DNA biosynthesis and cellular energy production. However, vitamin B12 deficiency leads to neurologic and psychiatric disturbances including depression, dementia, and a demyelinating myelopathy. Moreover, it’s also associated with other diseases such as pernicious anemia and other hematologic manifestation. Methods: After approval from Hebron Charitable Medical Center (HCMC), a retrospective study was carried out among patients at Charitable Medical Center (HCMC) in Hebron, Palestine. It was carried out over a period of one year and half starting from January 2013 till June 2014. Aim: This study was conducted to determine the prevalence of vitamin B12 among the patients of HCMC. Results: In general, a total of 305 patients screened for serum vitamin B12 levels were enrolled. There were 90 (29.5%) men and 215 (70.5%) women, there were 285 (93.4%) <60 years old and 20 (6.6%) >60 years old .There were 50 patients (16.4%) had vitamin B12 deficiency. Mean ± SEM levels of B12 in 305 subjects were observed to be 389.73.1±12.93 (range: 60 - 1432 pg/ml). Men had mean value of 423.11±30.17 (range: 60 - 1432 pg/ml) and women had 375.75±13.24 (range: 76 - 1292 pg/ml). Conclusion: This study had highlighted a number of patients that reveals Vitamin B12 deficiency according to gender and age. We recommend the necessary implementation of Vitamin B12 supplements for all men and women with any age.